2004
DOI: 10.1039/b412016g
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced selectivity in non-heme iron catalysed oxidation of alkanes with peracids: evidence for involvement of Fe(iv)O species

Abstract: Catalytic alkane oxidation with high selectivity using peracids and an (N4Py)Fe complex is presented and the role of [(N4Py)Fe(IV)=O]2+ species, molecular oxygen and hydroxyl radicals in the catalysis is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 9 publications
(10 reference statements)
4
29
0
1
Order By: Relevance
“…When treated with hydrogen peroxide 1 and 2 fail to generate the hydroperoxido intermediate as seen from a UV/Vis spectral study and no catalytic oxidation of alkanes is observed, which can be attributed to the formation of an inactive catalyst. [45] …”
Section: Catalytic Oxidations Of Hydrocarbons With [Ru(ntb/mntb)-cl 2mentioning
confidence: 97%
“…When treated with hydrogen peroxide 1 and 2 fail to generate the hydroperoxido intermediate as seen from a UV/Vis spectral study and no catalytic oxidation of alkanes is observed, which can be attributed to the formation of an inactive catalyst. [45] …”
Section: Catalytic Oxidations Of Hydrocarbons With [Ru(ntb/mntb)-cl 2mentioning
confidence: 97%
“…‐transfer is rate limiting. The {Fe IV O} species is assumed to be the only active species when hydrogen peroxide is replaced by peracids in the catalytic oxidation of cyclohexane 111a. The reaction is efficient under anaerobic conditions giving an increased alcohol/ketone reaction.…”
Section: Iron Bleaching Catalystsmentioning
confidence: 99%
“…The development of synthetic, biomimetic model compounds12 for non‐heme iron proteins, such as methane monooxygenase (MMO), has opened up a new approach in alkane activation chemistry 1c,e,g. 13, 14b,c,d Some of these compounds were shown to be valuable model precursors for high‐valent μ‐oxo diiron species 12b,d. 14 Iron acetate, pivalinate, and picolinate species present in alkane activating systems of the Gif III and Gif IV and GoAgg III types have been extensively characterized 15.…”
Section: Oxidation Of Cyclohexane Catalyzed By 2[a]mentioning
confidence: 99%